What are the success rates for CPR for cardiac arrest in the community with and without rescue breathing?. Issue 12 (December 2017) - Gilles, Ryan; Henbest, Daniel; Beasley, Britta
Abstract : EVIDENCE‐BASED ANSWER : For untrained bystanders instructed by a dispatcher, compression‐only cardiopulmonary resuscitation (COCPR) in adults improves survival to hospital discharge by 20% compared with cardiopulmonary resuscitation with rescue breathing (standard CPR). However, both techniques are associated with similar success if bystanders are not receiving dispatcher instruction (SOR: A, meta‐analysis of RCTs). Standard CPR is associated with slightly higher 1‐month survival rate than COCRP in mixed populations of children and adults (SOR: B, metaanalysis of cohort studies and single cohort study). CPR providers with prior CPR training should continue doing standard CPR, but lay providers instructed by dispatchers should do COCPR (SOR: C, expert opinion).